Sowing the seeds of biodiversity - Gew, Lai Ti *; Ser, Hooi Leng *; Long, Chiau Ming * (New Straits Times, 2023)
Malaysia is a megadiverse country, boasting a wealth of species, many exclusive to its shores. This biodiversity demands a holistic conservation strategy.